Optimizing Educational Facility Management: Key Strategies for Bridging the Quality Gap - Nurafni; Sriwardona; Rianawati (Al-Qalam Institue, 2025)
The study aims to understand how effective management impacts the quality of education and the challenges faced by educational institutions in managing these resources. This research adopts a qualitative approach, utilizing interviews and document analysis to gather data from educational institutions. The study examines the role of facilities and infrastructure in creating a conducive learning environment and investigates the obstacles faced, such as budget constraints, lack of competent human resources, and disparities between urban and rural schools. The findings reveal that optimal management of facilities and infrastructure directly contributes to improving the quality of education. Strategic efforts, including efficient use of space, submitting proposals for government assistance, and collaborating with the school committee, are critical in overcoming existing challenges. Additionally, the study highlights the importance of needs analysis in facility procurement to ensure resources are appropriately allocated. The study highlights that effective management of educational facilities requires the involvement of all school members. Schools should emphasize collaboration, strategic planning, and efficient resource use. Bridging the facility gap between urban and rural schools is crucial for improving education quality and achieving educational goals..